2021
DOI: 10.1136/rapm-2020-102132
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the soft-embalmed Thiel cadaver as a high-fidelity simulator of pressure during targeted nerve injection

Abstract: IntroductionAlthough administration of regional anesthesia nerve blocks has increased during the COVID-19 pandemic, training opportunities in regional anesthesia have reduced. Simulation training may enhance skills, but simulators must be accurate enough for trainees to engage in a realistic way—for example, detection of excessive injection pressure. The soft-embalmed Thiel cadaver is a life-like, durable simulator that is used for dedicated practice and mastery learning training in regional anesthesia. We hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 36 publications
2
9
0
Order By: Relevance
“…The imaging, needle insertion and injection procedures were performed by two operators, one a regional anesthesiologist and the other a PhD engineering student, trained previously to conduct ultrasound guided nerve injection on Thiel cadavers18 19 and pigs 20. We identified the radial, median and axillary nerves according to the schemata provided by Steinfeld et al 25…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The imaging, needle insertion and injection procedures were performed by two operators, one a regional anesthesiologist and the other a PhD engineering student, trained previously to conduct ultrasound guided nerve injection on Thiel cadavers18 19 and pigs 20. We identified the radial, median and axillary nerves according to the schemata provided by Steinfeld et al 25…”
Section: Methodsmentioning
confidence: 99%
“…First, histology studies characterized the microscopic anatomy of nerves13 14; delineated spread using a novel heparinised blood marker15 within adipocyte-containing neural compartments16 and questioned the value of extrapolating results obtained from different animal models 17. Second, Thiel cadaver studies identified the wide, log-normal distribution of pressure and force data at tissue interfaces18 and dependence of injection pressure on flow rate 19. Third, application of 40 MHz microultrasound of the axillary brachial plexus in anaesthetized pigs showed highly detailed anatomy and precise location of needle tips relative to the target nerve 20…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, our work has validated the physical and functional alignment of the Thiel embalmed cadaver simulator [10], developed and validated checklist and eye tracking metrics that reflect skills performance [11], introduced mastery learning and dedicated 1:1 training to regional anesthesia [5], measured learning curves using new needle technology [5], and showed translation of skills from cadavers to patients 3 weeks after training. We also used eye tracking to measure the performance of the simulators and patients [4].…”
Section: Current Evidencementioning
confidence: 99%
“…Abdelhadi, R. Vanstone and M. Oldman University Hospitals Plymouth NHS Trust, Plymouth, UK Chloroprocaine 2% is an ester local anaesthetic offering a shorter onset, duration of action, and offset than other commonly used agents, making it particularly suitable for ambulatory surgery. 1 Although established for short-acting spinal anaesthesia, it has only recently launched on the UK market for peripheral nerve block. 2 We evaluated recovery of motor function in patients undergoing awake surgery using chloroprocaine 2% for ambulatory hand trauma procedures.…”
Section: Recovery Of Motor Function In Ambulatory Hand Trauma Using C...mentioning
confidence: 99%